(untitled) (Bangladesh Journal of Botany, 2024)
Eighteen litchi genotypes were evaluated in this study for genetic advancement, heritability, variability, and association studies. The genotype ‘CHL-4’ exhibited maximum fruit weight (28.12 g), aril weight (14.00 g), aril thickness (9.65 mm) and seed weight (4.86 g). Fruit length (10.70 and 10.46%), panicle width (10.61 and 10.37%), and panicle length (15.75 and 15.45%) all had substantial phenotypic and genotypic coefficients of variation. All the metrics, with the exception of fruit diameter, aril thickness, seed weight, and number of fruits/panicle, showed higher heritability estimations with substantial genetic advances. In addition to being negatively correlated with fruit weight, aril weight, seed weight and pulp thickness, yield also showed a strong positive correlation with the number of fruits/panicle and aril percentage. Path analysis made the impact of different components on yield very evident. The maximum positive direct effect on yield at genotypic level was through fruit weight (10.120) followed by seed weight (4.070), panicle length (1.550), panicle girth (1.170) and negative direct effect via aril weight (-0.12.860) followed by panicle width (-11.830), fruit length (-6.290). In order to select a diverse parent for a subsequent breeding effort, cluster analysis assists in classifying comparable objects into appropriate categories. Therefore, the goal of the study was to confirm the genetic variability across genotypes of litchi and identify prospective features for the selection of genotypes that are superior. Bangladesh J. Bot. 53(3): 465-473, 2024 (September)